Household Indebtedness in the Context of the Financialization of Social Policies - Başak Işıl Alpar (İstanbul İktisat Dergisi)
Following governments and corporations, financial institutions and banks opened a new path for themselves through household indebtedness during the financialization process, which accelerated with neoliberalism and globalization and expanded the scope of inclusiveness. Regarding this mentality, this situation is related to the desire for control that emerged during the transition from natural philosophy to the scientific revolution. It is also related to developing an economic mentality that does not overlap with society and humanity by embracing capitalism’s theoretical foundations. In this context, quantitative and qualitative financialization strategies have emerged to cover people from almost every income group. Some of the people who are targeted by financialization through household indebtedness are also the people for whom these social policies exist. Therefore, this study aims to examine the transformative effect of the financial structure that provides income through household indebtedness on social policies and lending strategies developed for households. Result of the literature review reveals that welfare states and social inclusion are replaced by debtfare states and financial inclusion, respectively. Moreover, this situation is interpreted as the financialization of social policies. Financialization and lending strategies developed as part of financial restructuring strengthen market power while weakening the social state. Furthermore, households facing deficiencies in social state welfare provision and seeking individual loans to meet their basic needs constitute an indebted society.